Parents' and Teachers' Views about Suitable Future Jobs for Learners with High-Functioning Autism at a Special School - Mushambi, Charles; Diale, Boitumelo M; Sefotho, Maximus M; Eseadi, Chiedu (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
There appears to be limited information regarding studies exploring parents' and teachers' views on appropriate jobs for learners with high-functioning autism (HFA). This study is significant because its purpose was to explore parents' and teachers' views on suitable jobs for learners with HFA at a special school in Johannesburg, South Africa. This study also sought to explore parents' and teachers' opinions on vocational methods for supporting learners with HFA. An interpretive paradigm was used as part of the qualitative research methodology. The data were generated from 12 selected participants using purposive sampling, including six parents whose children had HFA and six teachers of learners with HFA from various phases of the school. Semistructured interviews and document analysis were used to generate the data. The data were analyzed via thematic data analysis. The study revealed that teachers and parents of learners with HFA see jobs such as waiters, athletes, swimmers, soccer players, basketball players, handball players, baking, cooking, drawing, artists, gardening, carpentry, building, plumbing, car-washing, driving, building websites, filing, laminating, playing video games, emailing, printing, and photographing as appropriate future jobs for learners with HFA. The findings revealed that vocational methods that are useful for developing jobs that are perceived as suitable for learners with HFA are gardening, sewing, cooking, selling food, and computer training through vocational shadowing involving multiple stakeholders. The study highlights the importance of a collaborative approach among stakeholders in developing individualized support plans for learners with HFA, focusing on identifying, nurturing, and placing them in suitable vocational roles for lifelong employment. Consequently, special education curricula for learners with HFA in South Africa should prioritize vocational skills and be collaboratively designed by all stakeholders. Keywords: Autism Spectrum Disorders; Parents; Teachers; High-Functioning Autism; Jobs